ANALYSIS OF KURIKULUM MERDEKA IN SEKOLAH PENGGERAK - Ali Muckromin; Anam Sutopo; Yulia Maftuhah Hidayati; Choiriyah Widyasari (Jurnal Cakrawala Pendas, 2023)
Education cannot be limited by space and time as Ki Hajar Dewantara said: "anyone can become a teacher and anywhere can be a class". Education will continue to experience development along with the changes or progress of the times. Since the beginning of independence until now, the curriculum in Indonesia has undergone 12 changes, the first Curriculum 1947; the second Curriculum 1952; the third Curriculum 1964; the fourth Curriculum 1968; the the fifth Curriculum 1975; the sixth curriculum CBSA 1984; the seventh Curriculum 1994; the eighth Curriculum 1999; the ninth Curriculum 2004 (CBSA); the tenth Curriculum 2006 (KTSP); the eleventh Curriculum 2013; And the twelfth “Kurikulum Merdeka” (2022). None other than the occurrence of various kinds of changes that are for the sake of realizing the goals of national education. The curriculum is also a very important organ in the body of education and has a very important role in determining the progress of education in Indonesia. This study aims to analyze the strengths and weaknesses of the “Kurikulum Merdeka” in primary drive schools, Wonosamodro District, Boyolali Regency. The method in this research is qualitative through a case study approach. The research shows the following results: there are several advantages of the “Kurikulum Merdeka” in “Sekolah Penggerak”, including: (1) Improving the quality of learning outcomes within 3 years; (2) Improving the ability and qualifications of school principals and educators; (3) Acceleration of school digitization (received 16 chromebooks); (4) Ability to act as a catalyst for change in other educational units; (5) Accelerating the achievement of Pancasila student profiles; (6) receive intensive assistance; (7) Obtaining additional budget in the form of BOS Performance for 3 years with a nominal value of Rp80,000,000,-/year. The weaknesses are (1) in terms of implementing the curriculum it cannot be fully implemented; (2) lack of human resources and an unstructured system (shortage of PAI & PJOK teachers); (3) The facilities and infrastructures that are less adequate. Pendidikan tidak bisa dibatasi oleh ruang dan waktu seperti yang dikatakan Ki Hajar Dewantara: “Siapapun bisa menjadi guru dan dimanapun bisa menjadi kelas”. Pendidikan akan terus mengalami perkembangan seiring dengan perubahan atau kemajuan zaman. Sejak awal kemerdekaan hingga saat ini, kurikulum di Indonesia telah mengalami 12 kali perubahan, yang pertama Kurikulum 1947; Kurikulum kedua tahun 1952; Kurikulum ketiga tahun 1964; Kurikulum keempat tahun 1968; Kurikulum Kelima 1975; kurikulum keenam CBSA 1984; Kurikulum ketujuh tahun 1994; Kurikulum kedelapan tahun 1999; Kurikulum Kesembilan 2004 (CBSA); Kesepuluh Kurikulum 2006 (KTSP); Kurikulum Kesebelas 2013; Dan yang kedua belas “Kurikulum Merdeka” (2022). Tidak lain adalah terjadinya berbagai macam perubahan demi terwujudnya tujuan pendidikan nasional. Kurikulum juga merupakan organ yang sangat penting dalam tubuh pendidikan dan mempunyai peranan yang sangat penting dalam menentukan kemajuan pendidikan di Indonesia. Penelitian ini bertujuan untuk menganalisis kelebihan dan kelemahan “Kurikulum Merdeka” di sekolah dasar berkendara Kecamatan Wonosamodro Kabupaten Boyolali. Metode dalam penelitian ini adalah kualitatif melalui pendekatan studi kasus. Penelitian menunjukkan hasil sebagai berikut: terdapat beberapa keunggulan Kurikulum Merdeka dalam “Sekolah Penggerak”, antara lain: (1) Meningkatkan kualitas hasil pembelajaran dalam waktu 3 tahun; (2) Peningkatan kemampuan dan kualifikasi kepala sekolah dan pendidik; (3) Percepatan digitalisasi sekolah (menerima 16 chromebook); (4) Kemampuan menjadi katalisator perubahan pada satuan pendidikan lainnya; (5) Percepatan pencapaian profil pelajar Pancasila; (6) mendapat pendampingan intensif; (7) Memperoleh tambahan anggaran berupa BOS Kinerja selama 3 tahun dengan nilai nominal Rp80.000.000,-/tahun. Kelemahannya adalah (1) dari segi implementasi kurikulum belum dapat dilaksanakan secara maksimal; (2) kurangnya sumber daya manusia dan sistem yang tidak terstruktur (kekurangan guru PAI & PJOK); (3) Sarana dan prasarana yang kurang memadai.